Bridging knowledge divides: Examining the dynamic landscape of ICT integration in Pakistan’s education sector - Sain, Zohaib Hassan; Lama, Alma Vorfi (American Journal of Education and Learning, 2024)
This study delves into information technology’s (ICT) effects on educational curriculum development, specifically focusing on the Pakistani context. The effects of information and communication technology (ICT) on various nations’ educational curricula are global. Integrating ICT into the academic sector is crucial to advancing educational planning in today’s technology-driven era. The research aims to scrutinize the utilization and influence of ICT in Pakistan’s educational landscape. A straightforward sampling procedure systematically gathered data from 385 Lahore city respondents spanning five public universities. The outcomes elucidate a substantial positive correlation between the availability and utilization of ICT and the enhancement of students’ knowledge and learning skills. The study accentuates the pivotal role of ICT in amplifying educational efficiency and underscores its significance in shaping policies within the education sector. The ramifications of the research extend to educators, policymakers, and stakeholders, emphasizing the imperative need to integrate ICT into educational practices to achieve optimal outcomes effectively. By acknowledging the affirmative impact of ICT on academic development, this study contributes valuable insights that can guide strategies for elevating educational quality and planning in the digital age, ensuring a more robust and technology-enabled educational system. This suggests that integrating ICT positively impacts educational effectiveness and is essential for informing policies within the education sector.